1)
y=x+2 домножим на 4
4y+x^2=8 сделаем перенос
4y=4x+8
4y=8 -x^2 вычтем второе из первого
4y-4y =4x+8 -(8 -x^2)
0=x^2+4x
x(x+4)=0 один из множителей равен =0
x1=0 ; y1=x1+2=0+2=2
x2=-4; y2=x2+2=-4+2=-2
отве+т (-4; -2) ; (0; 2)
2)
y^2+2x-4y=8
2y-x=2 домножим на 2
y^2+2x-4y=8
4y-2x=4 ; сложим уравнения
y^2+2x-4y + 4y-2x = 12
y^2=12
y1= -√12 = - 2√3
y1= √12 = 2√3
2y-x=2 ; x=2y-2
x1=2*(- 2√3) -2 = -2 - 4√3
x2=2* 2√3 -2 = -2 +4√3
ответ (-2 - 4√3 ; - 2√3) ; (-2 + 4√3 ; 2√3)
3)
x\2-y\3=x-y домножим на -4
2(x+y)-2(x-y)-3=2x+y упростим
-2x+4y/3=-4x+4y
-8y/3+2x=0 (1)
2x+2y-2x+2y-3=2x+y
4y -3 = 2x+y
3y -2x = 3 (2)
сложим (1) и (2)
-8y/3+2x +3y -2x =0 +3
-8y/3+3y =3
y (3-8/3)=3
y (9-8) / 3=3
y= 9
из уравнения (2)
3y -2x = 3 ; 2x =3y-3 ; x=3/2 *(y-1)
x= 3/2 *(9-1) =12
ответ (12; 9)
4)
3(x-y)-2(x+y)=2x-2y упростим
x-y/3-x+y/2=x/6+1 домножим на 6 и упростим
3x-3y-2x-2y=2x-2y
- 3y = x (1)
6x-2y-6x+3y=x+6
y=x+6 (2)
вычтем из (1) (2)
- 3y - y = x -(x+6)
-4y = -6
y= 3/2
тогда из (1)
- 3y = x ; x= -3 * 3/2 = -9/2
ответ (-9/2 ; 3/2)
Подробнее - на -
a2 = 3pi/4+2pi*k; cos a2 = -√2/2
cos(60 + a1) = cos 60*cos a1 - sin 60*sin a1 =
= 1/2*√2/2 - √3/2*√2/2 = √2/4*(1 - √3) = -√2(√3 - 1)/4
cos(60 + a2) = cos 60*cos a2 - sin 60*sin a2 =
= -1/2*√2/2 - √3/2*√2/2 = -√2/4*(1 + √3) = -√2(√3 + 1)/4
2) sin a = 2/3; cos b = -3/4; a ∈ (pi/2; pi); b ∈ (pi; 3pi/2)
cos a < 0; sin^2 a = 4/9; cos^2 a = 1-4/9 = 5/9; cos a = -√5/3
sin b < 0; cos^2 b = 9/16; sin^2 b = 1-9/16 = 7/16; sin b = -√7/4
sin(a+b) = sin a*cos b + cos a*sin b =
= 2/3*(-3/4) + (-√5/3)(-√7/4) = -6/12 + √35/12 = (√35 - 6)/12
cos(-b) = cos b = -3/4